Telemedicine system using mobile internet communication. Issue 2 (27th July 2020) - S., Saravanan; P., Sudhakar
Abstract : Purpose: Telemedicine is delivered to patient anywhere during emergency treatment care, and medical information is transferred from one site of patient to another site of specialist doctors by using mobile internet communication. Some rural areas have slow internet speed because of weak internet signal propagation from mobile towers. A good design of antenna is needed to improve mobile internet speed for big medial data transmission in telemedicine application. Hence, this paper aims to propose economically low-cost design of antenna. Design/methodology/approach: Telemedicine recommended to design the satellite frequency modulation dish (SAT FMD) antenna ( where in FM radio antenna, dish antenna are combined ) to improve the internet speed at Telemedicine system and Hospitals for purpose of Telemedicine communication and information for emergency treatment. Findings: In the proposed system, designed SAT FMD satellite-based antenna improved internet speed is achieved at 90.6% accuracy in this research method. Finding latitude and longitude angles to identify the patient location, nearest hospitals location and finding distance, shortest path routing between patient and hospital. Finding elevation, Azimuth, latitude, longitude, skew for alignment dish to focus satellite and mobile cell tower to improve internet speed at telemedicine area and hospitals and reduced transmission delay and nodal delay of big medical data. Social implications: The social awareness among people can be shared information of accident patient to communicate Hospital and Ambulance driver by internet mobile app tools and help find nearest hospitals to emergency treatment for accident people. Originality/value: This paper presents SAT FMD antenna model based on satellite dish antenna consisting of FM radio receiver antenna and dish antenna for telemedicine communication.